On the freedom to contract in the monitoring of economic groups - oumohammed, hayat (The journal of Teacher Researcher of Legal and political Studies, 2024)
The economic environment has recently seen the emergence of global economic conglomerates, creating a kind of unfair competition, which has prompted the Algerian legislator to promulgate a competition law prohibiting all forms of monopoly and agreements restricting competition. as well as bringing all forms of economic groupings under control, The agreement is the best way to complete the assembly and to place competition law under its control. And therefore it undoubtedly violates one of the general principles on which contracts are based, namely the principle of contractual freedom. The question that arises is the extent of the influence of the group control system on the principle of freedom to contract, and highlights the transformation of traditional principles of contracting, and how control of the concentration process contributes to violate these principles. This study concludes with a description and an analysis of the control system of economic groups in Algerian competition law.